Crafting Computational Counter-Media: Spatial Story Design of Housing (In)justice and Archival Challenges - Brett A. Halperin (Radical Housing Journal)
This piece is an update on the community-based design process behind the Anti-Eviction Mapping Project’s (AEMP) interactive digital story map documenting housing (in)justice during the Covid-19 pandemic. As housing insecurity escalated amid global lockdowns, AEMP volunteers began tracking housing protection legislation, justice actions, and eviction data while simultaneously collecting oral histories from tenants as acts of resistance. Through a critical reflection on leading the design process, I analyze how the initial map visualization evolved into a multimedia geographic information system through intentional community-based design. I synthesize the core priorities that emerged—accessibility, aesthetic sensibility, criticality, language justice, and usability—alongside the challenges of grassroots organizing, including resource constraints, technical limitations, volunteer burnout, and interpersonal conflict. Reflecting on these struggles and priorities, I provide an update on how computational counter-media can be crafted as community-driven counter-maps in pursuit of housing justice. This account offers insights into designing grassroots platforms that center tenant voices and challenge dominant narratives to reclaim digital spaces for community-driven media representation with ongoing archival challenges.